What characterises a useful concept of causation in epidemiology?. Issue 2 (1st February 2003) - Olsen, J
Abstract : It has recently been suggested that epidemiologists should avoid thinking of causes in deterministic terms. This would mean giving up the component-cause model in its original form. A model that has provided important contributions as to how we develop hypotheses, design our study, analyse data, interpret and communicate our results. The component-cause model has considerably more to offer than a simple probabilistic concept. What a causal model has to offer to the advancement of the discipline is equally important as the concept itself. It has been said that we should not hunt "the Holy Grail" (that is, determinism), if it does not exist. This line of reasoning neglects the fact that the "hunting" is more important than the "finding".